Communication Ethics of Criticism in the Public Space of Twitter Social Media - Arifan Efendi; Tessa Shasrini (Experimental Student Experiences, 2024)
This study aims to find out how communication ethics critiques in the public space of social media Twitter. This study uses a qualitative approach because in this study it describes the phenomena studied in the form of descriptions that show how communication ethics criticizes the public space of Twitter's social media. The subject in this study is social media twitter. The object of this study is the ethics of communication to criticize in the public space of Twitter's social media. This study uses secondary data. The results of this study indicate that the ethics of communication in conveying criticism on Twitter social media must pay attention to, among others: using good language, avoiding the spread of criticism that contains racism, pornography and acts of violence and propaganda, re-checking the correctness of information, respecting the work of others when conveying criticism either in the form of photos, writings or videos belonging to other people, it must include the source of the information. Communication ethics has a legal basis, namely Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Information and Electronic Transactions (UU ITE).